Innovation within Tradition : Joseph Ratzinger and Reading the Women of Scripture - McKenna, Mary Frances (Emerging scholars., 2015)
Innovation within Tradition is an exploration of the meaning and implications of Joseph Ratzinger's biblical interpretation of the women of salvation history. Mary Frances McKenna argues that Ratzinger's work, through his development and refinement of the church' tradition, brings the important role and significance of the female characters of Scripture to the fore by placing them at the heart of Christian faith. Explicating the pope emeritus's concept of a "female line in the Bible," which has a profound impact on the meaning and interpretation of the women of salvation history, the volume shows that this concept illustrates the practical value and creative nature of his approach to theology and biblical interpretation. Pivotal to the argument are questions around the findings on the notion of person, feminist theology, salvation history, and Mary, as well as the use of history in theology and biblical interpretation and the potential for the continuing development and deepening of the church's comprehension of the meaning of revelation. The book advances a constructive approach, in coordination with these questions, for a Trinitarian theology of society, addresses old theological issues anew, and provides a starting point for an interdenominational understanding of Mary.